Determining Factors of Self-Management in Hypertension Patients: Literature Review - Priyanto, Priyanto; Tiku Tondok , Anton (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2026)
Hypertensive patients who have good self-management skills can manage their disease in a better and more beneficial way. Each patient diagnosed with hypertension has different self-management in managing their blood pressure. This study aims to determine the determinants of self-management in hypertensive patients. This research method is a literature review using the PICOS method with the PRISMA reporting framework that includes journal analysis in the PubMed database, Cumulative Index to Allied Health and Nursing Research [CINAHL], Embase, and Web of Science) until 2025. Journals were analyzed in four stages, including identification, screening, eligibility, and analysis. Journal findings were then analyzed descriptively with the support of related journals or theories. The journal findings were then analyzed descriptively, supported by related journals and theories. Five articles were included in the review and analyzed using descriptions of the determinants of self-management in hypertension patients. Ten factors were identified as contributing to self-management in hypertension patients. Several factors that determine and influence self-management in hypertension patients were identified, including age, occupation, smoking and medication habits, marital status, duration of hypertension, self-efficacy, family history of hypertension, level of knowledge, and family support.